Whether or not to enroll, and stay enrolled? A Tanzanian cross-sectional study on voluntary health insurance - Alphoncina Kagaigai; Amani Thomas Mori; Amani Anaeli; Sverre Grepperud (Elsevier, 2023)
Lower-middle income countries (LMICs) have invested significant effort into expanding insurance coverage as a means of improving access to health care. However, it has proven challenging to fulfill these ambitions. This study investigates to what extent variables associated with the enrollment decision (stay never-insured or enroll) differ from variables associated with the dropout decision (stay insured or drop out). A cross-sectional survey that included 722 households from rural districts in Tanzania was conducted and multinomial logistic regressions were performed to determine the associations between independent variables and membership status (never-insured, dropouts, or currently insured). Both the decision to enrollment and the decision to drop out were significantly associated with the presence of chronic disease and perceptions about the quality of services provided, insurance scheme management, and traditional healers. The effect of other variables, such as age, gender and educational level of the household head, household income, and perceptions about premium affordability and benefit-premium ratios, varied across the two groups. To improve voluntary health insurance coverage, policymakers must simultaneously increase the enrollment rate among the never-insured and reduce the dropout rate among the insured. Our conclusions suggest that policies to increase insurance scheme enrollment rates should differ for the two uninsured groups.